Profil Tempat Tumbuh Sarang Semut (Myrmecodia spp.) Di Distrik Manokwari Selatan Papua Barat - Enderia Wabia; Rima H. S. Siburian (EnviroScienteae, 2019)
Papua has a very high diversity of flora species, one of which is a type of Sarang Semut. Different growing conditions will affect the level of diversity of plants. For that information about the place to grow Ant Plant is needed as basic information for the development of the cultivation of Ant plants. The method used is descriptive method with field observation technique. The results showed that the type of ant nest plant found in South Manokwari was a type of Myrmecodia pendans and Myrmecodia cf. schlechteri. Both of these species do not grow evenly in all study locations even at the same height, this plant has a characteristic growing place: it grows on host trees that are not slippery, predominantly in areas near rivers, requiring sunlight or in open areas. The position of growing on trees, the type of Myrmecodia cf. schlechteri was found to grow only on the main stem of the host plant, while Myrmecodia pendans were found in the branching area. Thus, even if the ant nest plant is able to grow in the lowlands to high, this specific condition is also needed for this plant to develop.